PENGGUNAAN METODE PEMBELAJARAN DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN PAI POKOK BAHASAN MEMBERSIHKAN NAJIS SISWA KELAS VII SMP ISLAM PAGAK KABUPATEN MALANG - Alfiyatul Ula; Mohammad Afifulloh; Yorita Febry Lismanda (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
The lack of insight into information in theory and practice and competence possessed by teachers to explore their ability to choose learning methods that are creative, innovative, right on target according to conditions in class to improve learning outcomes is a prblem that educators really need to understand. With the above problems researchers try to help overcomee them by giving an overview and examples of actions in learning. This study aimed to find a solution to the subject matter of unclean cleaning by applying demonstration methods to improve learning outcomes of class VII students of Pagak Islamic Middle School Malang Regency. This study only uses 1 cycle with 2 meetings consisting of 4 stages, namely action planning, action implementation, observation and reflection and the number of student subject to action is 22. At the pre cycle stage the number students completed is 9 students with percentage of 41%. While the implementation of the first cycle increased to 19 student who completed the study with percentage 86%. Based on these results it can be concluded that the application of the demonstration method can improve the learning outcomes of class VII Pagak Islamic Middle School Malang Regency.